Vitamin D Deficiency in Menopausa Women - Amonova Madina Furkatovna (Peerian Journals Publishing, 2022)
This article discusses the effect of vitamin D levels on bone mineral density in menopausal women. In addition, the effects of vitamin D on menopause have been studied. The aim of this review is to summarise the evidence linking vitamin D to bone health outcomes in menopausa women. A plethora of scientific evidence globally suggests that large proportions of people have vitamin D deficiency and are not meeting recommended intakes. Older adults are at particular risk of the consequences of vitamin D deficiency owing to a combination of physiological and behavioural factors. Epidemiological studies show that low vitamin D status is associated with a variety of negative skeletal consequences in older adults including osteomalacia, reduced bone mineral density, impaired Ca absorption and secondary hyperparathyroidism. There seems to be inconsistent evidence for a protective role of vitamin D supplementation alone on bone mass. However, it is generally accepted that vitamin D (17·5 μg/d) in combination with Ca (1200 mg/d) reduces bone loss among older white subjects. Evidence for a benefit of vitamin D supplementation alone on reducing fracture risk is varied. According to a recent Agency for Healthcare Research and Quality review in the USA the evidence base shows mixed results for a beneficial effect of vitamin D on decreasing overall fracture risk. Limitations such as poor compliance with treatment, incomplete assessment of vitamin D status and large drop-out rates however, have been highlighted within some studies. In conclusion, it is generally accepted that vitamin D in combination with Ca reduces the risk of non-vertebral fractures particularly those in institutional care. The lack of data on vitamin D and bone health outcomes in certain population groups such as diverse racial groups warrant attention.
Keywords: Menopause; menopausal period; Vitamin D; Calsium